Rámcová rozhodnutí a zásada vzájemného uznávání rozhodnutí v trestních věcech - Polák, Přemysl, 1974- (2006)
This work examines the framework decisions as one of the legal acts under Article 34 of the Treaty on European Union, the principle of mutual recognition of decisions in criminal matters, which, according to the Presidency Conclusions of Tampere European Council of 15th and 16th October 1999, should become the cornerstone of judicial co-operation in criminal matters, and the relationship between them.